Determinan Cakupan Imunisasi Dasar Lengkap pada Penerima Program Keluarga Harapan - Wulansari, Wulansari; Nadjib, Mardiati (Jurnal Ekonomi Kesehatan Indonesia, 2019)
Poverty is a multidimensional social problem and related to the problems of health, education and other social welfare. National Basic Immunization Coverage (IDL) reached 57.9%, with 32.9% was incomplete and 9.2% were not immunized, while national coverage indicators were at least 90%. This study aims to determine the determinants that affects basic complete immunization coverage for babies receiving the Family Hope Program (PKH). The study design used was cross sectional. The research was located in 34 provinces. The total population is 9,205 respondents using secondary data from the National Socio-Economic Survey (Susenas) in 2017. The research shows that the achievement of complete basic immunization is 97.34% and 2.66% is incomplete. The results shows that age and marital status are positively related and significantly influence the basic immunization coverage, while education and employment variables are significantly associated but negatively related to basic immunization coverage. PKH has provided opportunities and access to poor households in implementing a complete basic immunization program. So it is necessary to intensify the supervision of young mothers, divorced mothers and working mothers to boost knowledge, build awareness, maintain and strengthen related behav ioral changes, health and care to increase the coverage of basic immunization in infants.